Whirl-flutter control via piezoelectric shunt damping effect - Haramura Bastos, Sérvio Túlio Suenai [UNESP]; de Vasconcellos, Rui Marcos Grombone [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The whirl-flutter phenomenon is an aeroelastic instability that must be predicted and controlled during the design of a propeller-driven aircraft. Commonly, propeller propulsion systems attached to wing structure are susceptible to this phenomenon, especially when considering large rotor diameters, such as vertical take-off and landing (VTOL) aircraft. Depending on the cruise speed among several parameters, a diverging precession motion occurs in the rotor, in a combination of structural, aerodynamic and gyroscopic effects, influencing the design of rotors, wings and pylons. Additionally, aeronautical structures always will present a certain level of nonlinear behavior, due to material properties, junctions and articulations that must be considered. With the advent of modern air mobility, a better understanding of such phenomenon, including nonlinear behaviors and the possible control techniques to increase the stability margins becomes important. Therefore, the present research proposes a passive control technique based on the piezoelectric shunt damping effect, in a unimorph configuration connected to the structure, which presents a hardening nonlinearity. Results shows that the presence of the piezoelectric material connected to a load resistance can postpone the flutter speed, improving the system’s stability and reducing the amplitude of oscillation. A range of optimal load resistances, over which the harvested power is maximized and the passive control is more effective is obtained. Additionally, the nonlinear hardening effect provides a limit cycle oscillation in the post-flutter regime.